Kewenangan Hakim untuk Melakukan Intervensi terhadap Kewajiban Kontraktual Berdasarkan Asas Iktikad Baik - Ridwan Khairandy (Fakultas Hukum Universitas Islam Indonesia, 2000)
Under the article 1338, section 3 of CMI Law Code, it is stated that an agreement shouid be implemented on the basis of goodwill because it is one of the important principles in Contract Law. However, the notion of goodwill is so abstract that it is whether related to a matter of law or moral. This article will propose a description of the goodwill -when and where itiscoming up-, its functions in implementing the agreement, and how the authorities of the judge toget involved towards the contract duties on the strength of the goodwill principles.